1976
DOI: 10.1136/ard.35.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Single daily dose corticosteroid treatment.

Abstract: . (1976). Annals ofthe Rheumatic Diseases, 35,[73][74][75][76]. Single daily dose corticosteroid treatment. Thirteen patients with rheumatoid or psoriatic arthritis who had not previously received corticosteroids were treated with prednisolone in a single dose each morning. Insulin-hypoglycaemia tests were performed before starting steroids in each patient, and again at the conclusion ofthe study in twelve of the thirteen (duration of steroid treatment 8-40 m). There was no difference in the mean basal or peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

1979
1979
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 14 publications
0
13
1
Order By: Relevance
“…Pituitary gland ACTH secretion may also be impaired. In contrast to our ¢ndings, Myles et al (26) reported a normal plasma corticosteroids response to ITT 20 years ago. But in that study the patient population was not characterized su¤ciently and diagnostic criteria for RA were not reported.…”
Section: Discussioncontrasting
confidence: 99%
“…Pituitary gland ACTH secretion may also be impaired. In contrast to our ¢ndings, Myles et al (26) reported a normal plasma corticosteroids response to ITT 20 years ago. But in that study the patient population was not characterized su¤ciently and diagnostic criteria for RA were not reported.…”
Section: Discussioncontrasting
confidence: 99%
“…Of the 25 studies excluded from either metaanalysis, 12 did not randomize subjects (8,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), 3 used an average corticosteroid dose >15 mg/day (38,40,41), and 7 were of <3 months' duration (31,35,(42)(43)(44)(45)(46). Six other studies were excluded: 1 contained outcome measures which were not comparable to those of the other 30 …”
Section: Resultsmentioning
confidence: 99%
“…Degree of adrenocortical suppression is known to be influenced by treatment duration, the type of steroid employed and its dosage, the administration route, and even by the time of day of the administration [13,14]. However, adrenal response in patients treated with glucocorticoids shows little correlation with dose or treatment duration [15,16].…”
Section: Discussionmentioning
confidence: 99%